1993
DOI: 10.1002/art.1780360215
|View full text |Cite
|
Sign up to set email alerts
|

Increased production of soluble CD23 in rheumatoid arthritis, and its regulation by interleukin‐4

Abstract: Objective. To assess CD23 status in rheumatoid arthritis (RA) patients, as defined by the levels of CD23 expression on peripheral blood mononuclear cells (PBMC), the levels of soluble CD23 (sCD23) in sera, and the production of sCD23 by PBMC cultures and its regulation by interleukin‐4 (IL‐4). Methods. CD23 expression as determined by double fluorescence‐activated cell sorter analysis and sCD23 production as determined by immunoradiometric assay were investigated in 24 RA patients and 21 controls. Soluble CD23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 38 publications
(18 reference statements)
3
29
0
Order By: Relevance
“…In addition, CD23 ligation did not affect the production of other cytokines such as macrophage-CSF (data not shown) indicating that CD23 stimulation cannot be considered as nonspecific. Finally, our data extend those of Donelly et al [20] and Chomarat et al [22], demonstrating that IL-10 production by human macrophages can also be obtained after ligation of the CD23 molecule and, thus, could play an important role in the regulation of CD23-dependent immune and inflammatory responses.…”
Section: Resultssupporting
confidence: 87%
“…In addition, CD23 ligation did not affect the production of other cytokines such as macrophage-CSF (data not shown) indicating that CD23 stimulation cannot be considered as nonspecific. Finally, our data extend those of Donelly et al [20] and Chomarat et al [22], demonstrating that IL-10 production by human macrophages can also be obtained after ligation of the CD23 molecule and, thus, could play an important role in the regulation of CD23-dependent immune and inflammatory responses.…”
Section: Resultssupporting
confidence: 87%
“…Results with very sensitive IL-4 assays indicated that activated RA whole blood cells produced more IL-4 than did controls, and with a higher IL-4:IFNy ratio. Such findings are consistent with the increased produc tion in blood as well as in activated peripheral blood mononuclear cell supernatants of soluble CD23, the production of which is enhanced by IL-4 (56). results are in contrast to those found in the RA syno vium, where a Thl pattern is predominant.…”
Section: Thl/th2 Cytokine Balance In Arthritissupporting
confidence: 88%
“…52,78 On the other hand, high levels of sCD23 have been detected in serum and synovial fluids of patients with rheumatoid arthritis and associated with worsening of the disease. [79][80][81] Synovial macrophages also express high levels of CD23 and its counter-ligands CD11b and CD11c. 80,82 These data suggest that an interaction of sCD23 or CD23 expressed on macrophages with CD11b or CD11c could play a major part in production of MIP-1␣ and MIP-1␤ in the joint and may therefore constitute an important mechanism sustaining continuous recruitment of inflammatory cells and maintaining chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%